Effect of short fibers orientation on mechanical properties of composite material – fiber reinforced concrete - Lusis, Vitalijs; Krasnikovs, Andrejs; Kononova, Olga; Lapsa, Videvuds-Arijs; Stonys, Rimvydas; Macanovskis, Arturs; Lukasenoks, Arturs (Journal of Civil Engineering and Management, 2017)
Traditional fiberconcrete structures have fibres in the mix oriented in all spatial directions, distributed in the structural element volume homogenously, what not easy to obtain in practice. In many situations, structurally more effective is the insertion of fibres into the concrete structural element body by forming layers, with a predetermined fibre concentration and orientation in every layer. In the present investigation, layered fibre concrete is under investigation. Short steel fibres were attached to flexible warps with the necessary fibres concentration and orientation. Warps were placed into the prismatic mould separating them by concrete layers without fibres. Prisms were matured and tested under four-point bending. The bending-affected mechanical behaviour of cracked fibre concrete was simulated numerically by using a developed structural model. Comparing the simulation results with experimental data, material micromechanical fracture mechanisms were analysed and evaluated.